Human monocytes and macrophages undergo M1-type inflammatory polarization in response to high levels of glucose - Torres-Castro, Israel; Kzhyshkowska, Julia (Immunology letters, 2016)
Emerging data suggest that elevated glucose may promote inflammatory activation of monocytic lineage cells with the ability to injure vascular endothelial tissue of diabetic patients, however evidence in primary human monocytes and macrophages is still insufficient. We investigated the effect of high glucose concentration on the inflammatory capacity of human macrophages in vitro and examined whether similar responses were detectable in circulating monocytes from prediabetic patients. Primary monocytes were isolated from healthy blood donors and differentiated into macrophages. Differentiated macrophages were exposed to normal levels of glucose (NG), high glucose (HG) or high mannitol as osmotic pressure control (OP) for three days. Using PCR, ELISA and flow cytometry, we found that HG macrophages showed overexpression of CD11c and inducible nitric oxide synthase as well as down-regulation of arginase-1 and interleukin (IL)-10 with respect to NG and OP macrophages. Consistent with in vitro results, circulating monocytes from hyperglycemic patients exhibited higher levels of CD11c and lower expression of CD206 than monocytes from normoglycemic controls. In subjects with hyperglycemia, elevation in CD11c+ monocytes was associated with increased obesity, insulin resistance, and triglyceridemia as well as low serum IL-10. Our data suggest that human monocytes and macrophages undergo M1-like inflammatory polarization when exposed to high levels of glucose on in vitro culture conditions and in patients with hyperglycemia. These results demonstrate that excess glucose has direct effects on macrophage activation though the molecular mechanisms mediating such a response remain to be elucidated.
Available online 4 June 2016
Gesehen am 02.07.2019